Pemberian Larutan Gula Garam dan Istirahat Pendek dalam Menurunkan Beban Kerja Pekerja Bagian Produksi Perusahaan Roti â€Xâ€ Kota Semarang - Widjasena, Baju (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2004)
ABSTRACK Background : Hot climate can increase body temperature, and then increase skin blood flow, heart beat rate, blood pressure, sweat rate and decrease gastrointestinal function. High sweat rate causes water-electrolyte imbalance in the body. Because of water-electrolyte imbalance, the bodyÂ felt to dehidration. In dehydration, the work pulse will arise andÂ make the work load arised. At â€œXâ€™ Bakery, The climate over the threshold level, so the worker suffer dehydration. In order to cope the problems, the study about water-electrolyte consumption and short pauses was done. The aim of this study was to know the effects of carbohydrate-electrolyte consumption and short pauses to work load. Mehtods : The design of the study was Within-subject design with 16 subjects (8 man & 8 women) .There was two treatment in this study. Work load was determined by measure the work pulse with ten pulses method. The data was analyzed with T-paired Test (a = 0.05). Results : The result showed that carbohydrate-electrolyte intake and short pauses can significantly decrease work pulse 42,13% (p<0,05) . Conclusion : Based on the result, it is concluded that water-electrolyte intake and short pauses can significantly decrease the work load . It is suggested that worker and management has to improve the intervention Â Keywords : carbohydrate-electrolyte solution intake, short pauses, hot climate, worker